implementasi knowledge Management pada Badan Pemerintah Sektor Minyak dan Gas Bumi - , Hendratmi Susilowati ([Yogyakarta] : Universitas Gadjah Mada, 2011)
BPMIGAS is a government body that sign, implement, and also take control of Production Sharing Contract. The aim of the research are to identify the type and quality of knowledge management, to understand the quality of learning, how to manage the knowledge, to identify he knowledge development, how to acquire and sharing the knowledge, and finally to recommend BPMIGAS in building the knowledge management. The theories and data were obtained through literature study and survey. Literature study has been done to get understanding on theories related to knowledge management. Analysis also has been done to BPMIGASâ blue print instead of book reference. To identify quality of learning and knowledge management implementation in BPMIGAS, survey has been done to organizationâs employees. Result of this research will recommend BPMIGAS how to implement knowledge management. This recommendation will include organization structure, leadership, how to acquire knowledge, storing, and also leveraging the knowledge.